Eksplorasi Etnomatematika Upacara Adat Pernikahan untuk Pembelajaran Matematika Di Desa Sidareja Kabupaten Cilacap - Budi Wahyu Pertiwi; Kusno Kusno; Gunawan Gunawan; Akhamad Jazuli (STKIP Singkawang, 2024)
The wedding process in Sidareja village, Sidareja District, Cilacap Regency is carried out using a unique and rich traditional ceremony with a meaning that is still thick with Javanese customs. However, this culture is still not widely used to strengthen learning, especially in mathematics learning, so by using ethnomathematical studies, it is hoped that it can clarify the study of the traditional culture of marriage in Sidareja village to be used in learning at school. The purpose of this study is to explore mathematical objects contained in wedding customs in Sidareja Village, Cilacap Regency, Central Java Province. The method used in this study is a descriptive qualitative method. The data collection technique in this study uses documentation, interviews, and observations. This research was carried out by exploring the sources of activities around traditional wedding ceremonies in Sidareja starting from: Preparation, Premarital Ceremony to Panggih Ceremony. The mathematical aspects that are explored include how Preparation (determining the wedding day) is included in the measurement material starting from counting in the concept of division, addition, and numbering. In addition, it was also presented a study of learning about flat figures, namely with the form of flat shapes such as rectangles, parallelograms, triangles, in terms of many, and rhombus found in majang tarub, sindur cloth, chitak, paes, keris-kerisan, kuluk, and suweng which are used in traditional wedding ceremonies in Sidareja village, Cilacap Regency, Central Java Province